The Impact of Trimurti's Intrinsic and ‎Extrinsic Motivation on Pondok Modern ‎Darussalam Gontor - Muhammad Al Mighwar (Universitas Darussalam Gontor, 2022)
Until now Pondok Modern Darussalam Gontor (PMDG) is still surviving, sustainable, and quality with several national and international recognition. Behind the readiness and success of PMDG, there is an initial motivation of the Trimurti founder of Gontor (hereinafter referred to as Trimurti) which is quite interesting to be studied as The Lessons Learned, especially for other pesantren Kiai. This study aimed to reveal the secrets of intrinsic and extrinsic motivation of Trimurti and its implications for PMDG. This study was a qualitative type, where data was collected using mixed techniques, namely field research and literature research. The data was written in descriptive, analytical, and historical methods through five stages, namely; selection of topics, heuristics, verification, interpretation, and 'historiography'. This research relies on five theories, namely; the Theory of Anatomy of Human Motivation, the Theory of Implications, the Trimurti Theory, the Kiai Theory, and the Modern Pesantren Theory. This study found that the intrinsic motivation of Trimurti includes the local and regional microscale, and their extrinsic motivation includes the national mesoscale and global macroscale which has positive implications in the form of selective protection actions of three pesantren systems and projections of four modern systems in PMDG that contribute extraordinary to the nation, the country, even the world. The author considers Trimurti to be the time to become the Role Model of Lessons Learned and receive the National Hero Title award in the momentum of a century of PMDG (1926-2026).